Efforts of Tionghoa Ethnic Groups to Strengthen Good Character Through the Incremental Change Approach - Nufus, Ahmad Busrotun; Mazid, Sukron (ASANKA : Journal of Social Science and Education, 2025)
Strengthening character in a multicultural society is a challenge amidst the current of globalization that has the potential to erode noble values. This study examines how the Tionghoa Ethnic community in Indonesia maintains and strengthens good character sustainably through an incremental change approach, namely changes in values, attitudes, and behaviour that occur gradually but consistently. Using descriptive qualitative methods and case study designs in three multicultural cities, data were collected through in-depth interviews, participant observation, and documentation studies of family practices and socio-religious organizations. The results show that character strengthening is carried out through two main strategies: (1) internalizing values such as hard work, responsibility, and integrity in everyday life; and (2) awareness, adaptation, and character application without losing cultural identity. The gradual character transformation produces a resilient, empathetic, and pro-social young Tionghoa generation. These findings prove that incremental change is effectively applied as a community culture-based character-building approach.